Color tunable photoluminescence properties in Eu3+ doped calcium bismuth vanadate phosphors for luminescent devices. Issue 12 (15th August 2019) - Kaur, Harpreet; Jayasimhadri, M.
Abstract: Single phase Eu 3+ activated calcium bismuth vanadate (CaBiVO5 ) phosphors have been successfully synthesized using solid state reaction method. X-ray diffraction (XRD) analysis confirms the pure phase formation and scanning electron microscope (SEM) micrographs exhibit inhomogeneous particle formation with irregular morphology of Eu 3+ doped CaBiVO5 (CBV) phosphor. The photoluminescence excitation (PLE) spectrum indicates significant absorption in the ultraviolet (UV) and near ultraviolet (n-UV) spectral region for un-doped CBV sample, whereas Eu 3+ doped CBV phosphors reveal various sharp absorption bands in n-UV and blue region along with host absorption bands. Trivalent europium activated CBV phosphors under 342 nm excitation exhibit dominant red emission peak at 613 nm wavelength accompanied by weak broadband originating from VO4 groups, whereas the phosphors under 464 nm excitation, exhibit similar emission profile with most intense one centered at 613 nm by excluding host emission bands. The energy transfer mechanisms and the probable cause for concentration quenching beyond 4.0 mol% of Eu 3+ ions concentration have been discussed in detail. The CIE chromaticity coordinates for the optimized phosphor, (0.551, 0.398) and (0.639, 0.358), situated in the reddish-orange and red region under 342 and 464 nm excitations, respectively. The CIE coordinates calculated based on the emission spectra measured under 464 nm excitation are close to the commercial phosphor Y2 O2 S: Eu 3+ (x = 0.622 and y = 0.351). All the above mentioned results support the utilization of Eu 3+ doped CBV phosphor as a potential red emitting component for luminescent devices.